FABRIKASI MIKROSFIR UO2 MENGGUNAKAN TEKNIK AERASI - Rachmawati, Meniek; Mutiara, Etty; Yulianto, Tri (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
It has been developed a fabrication process of low density UO2 microspheres for direct feed in pelletization process of PHWR advanced reactor fuel. The fabrication has been implemented by a sol-gel method using aeration technique on the sol / broth with external methods and three variations of gelation. In the aeration technique, broth is directly prepared in gelation mode without one night settling time. The aeration technique is the opposite of the deaeration technique, which is used in fabricating microspheres HTGR fuel. The broth which has been prepared with a mole ratio of NO3 / U between 1.5 to 1.7 with pH solution of 1.6 and viscosity between 630-660 cP directly to be gelated in three ways of gelation. The process of both gelation method 1 and method 2 is implemented by passing through the broth to a dispersion nozzle with 1 mm of diameter which is vibrated by an electromagnetic vibrator at 150 Hz with medium for free fall droplet differently before entering into a solution of NH4OH, while the gelation method 3 implemented manually. The wet UO2 microspheres derived from the three ways of gelation above are treated by heating process at the same way that is dried at a temperature of 85 ºC and 220 ºC each respectively for 1 hour, followed by a calcination process of microspheres UO2 for 1 hour at a temperature of 500 ºC in gaseous medium of O2 and a reduction process at a temperature of 600 ºC in gaseous mixture of N2 and H2 medium for 1 hour. The UO2 microspheres gelation of method 3 are chosen to be sorted and characterized. The characterization results provide the characteristics data of UO2 microspheres in the form of microspheres diameter of 900 μm, tap density of 1.90 g/cm3 and specific surface area of 6 m2/g. The results of the analysis and characterization are then compared to other data of other research so that it can be concluded that the use of such an aeration technique on the broth can produce low density UO2 microspheres that qualify as direct feed for fuel pelletization process of the advanced PHWR and advanced PWR. The fabrication using the aeration technique with gelation method 2 has the greatest opportunity to produce UO2 microspheres with a high production rate and certain characteristics if it is implemented by resetting the rate of dispersion and the free fall droplet duration.